Antioxidant activity guided separation of major polyphenols of marjoram (Origanum majorana L.) using flash chromatography and their identification by liquid chromatography coupled with electrospray ionization tandem mass spectrometry†. Issue 22 (30th September 2014) - Hossain, Mohammad B.; Camphuis, Gabriel; Aguiló‐Aguayo, Ingrid; Gangopadhyay, Nirupama; Rai, Dilip K.
<x xml:space="preserve">Abstract</x> Marjoram extracts have been separated into polar and nonpolar parts using liquid–liquid extraction. Both polar and nonpolar parts of the extracts were further fractionated by flash chromatography. The obtained fractions (90 polar and 45 nonpolar fractions) were investigated for their antioxidant activities by 2, 2‐diphenylpicrylhydrazyl and ferric ion reducing antioxidant power assays. A direct, positive, and linear relationship between antioxidant activity and total phenolic content of the fractions was observed. Based on antioxidant and total phenolic content data, the three fractions with the high antioxidant activities from polar and nonpolar part of the extract were analyzed for their constituent polyphenols by liquid chromatography coupled with electrospray ionization tandem mass spectrometry. Compounds were identified by matching the mass spectral data and retention time with those of authentic standards. Identification of the compounds for which there were no "in‐house" standards available was carried out by accurate mass measurement of the precursor ions and product ions generated from collision‐induced dissociation. Rosmarinic acid was found to be the strongest antioxidant polyphenol conferring the highest antioxidant activity to fractions 47 and 17 of polar and nonpolar part of the extract, respectively. The identification of the rosmarinic acid was further confirmed by 1H NMR spectroscopy.